Restoring the teeth after endodontic treatment by posts and chemical curing composite material (Эндодонтия Today, 2020)
Restoration of teeth after endodontic treatment is one of the most important steps in the practice of dentist-orthopedist. The strength of the remaining tooth structure depends on the amount of remaining dentin, and resistance to fracture increases with the thickness of the dentin. Using the «golden rule» setting the posts into the root canal of a tooth can avoid many complications, thereby improving the quality of their work and increase its service life. It was built up 76 stumps of teeth by the method chosen by the authors. Restoration of tooth stump by composite material with a cap-formers can significantly improve the quality of treatment and to reduce the number of complications in the long-term period after prosthesis.